Maternal disability and newborn discharge to social services: a population-based study - Grant, Claire; Lunsky, Yona; Guttmann, Astrid; Vigod, Simone; Sharpe, Isobel; Fung, Kinwah; Brown, Hilary (International Journal of Population Data Science, 2024)
Introduction Removing a child from their family is the option of last resort for social services. However, decisions to place children into care are occurring more frequently and earlier in children's lives, with newborn discharge to social services being a particular concern due to the effects of mother-newborn separations on child development. Women with disabilities face negative assumptions about their parenting capacity, but little is known about their rates of newborn discharge to social services. Objectives To examine the risk of discharge to social services among newborns of women with and without disabilities. Methods We conducted a population-based cohort study of singleton livebirths in Ontario, Canada, 2008-2019. We used modified Poisson regression to estimate the relative risk (RR) of discharge to social services immediately after the birth hospital stay, comparing newborns of women with physical (n = 114,685), sensory (n = 38,268), intellectual/developmental (n = 2,094), and multiple disabilities (n = 8,075) to newborns of women without a disability (n = 1,221,765). Within each group, we also examined maternal sociodemographic, health, health care, and pregnancy-related characteristics associated with the outcome. Results Compared to newborns of women without disabilities (0.2%), newborns of women with physical (0.5%; aRR 1.53, 95% CI 1.39-1.69), sensory (0.4%; aRR 1.34, 95% CI 1.12-1.59), intellectual/developmental (5.6%; aRR 5.34, 95% CI 4.36-6.53), and multiple disabilities (1.7%; aRR 3.09, 95% CI 2.56-3.72) had increased risk of being discharged to social services after the birth hospital stay. Within each group, the strongest predictors of the outcome were young maternal age, low income quintile, social assistance, maternal mental illness and substance use disorders, inadequate prenatal care, and neonatal morbidity. Conclusions Newborns of women with disabilities are at increased risk of being discharged to social services after the birth hospital stay. These findings can be used to inform the development of tailored supports for new mothers with disabilities and their infants.